Schematic eye-gaze cues influence infants’ object encoding dependent on their contrast polarity - Christine Michel (Nature Portfolio, 2017)
Abstract We examined infants’ sensitivity to eye-gaze direction and its influence on object processing in 4-month-old infants by manipulating low-level properties of gaze cues. Infants were presented with two kinds of stimuli that either did or did not cue novel objects. The movement of a schematic image of two eyes (two black circles each moving on a white oval background) led to an enhanced processing of the cued object. A cue with reversed polarity (two white circles each moving on a black oval background) elicited distinctly weaker effects. Results highlight infants’ specific sensitivity to isolated eye gaze which furthermore facilitates object encoding. It is suggested that this sensitivity relies on the typical perceptual pattern of eyes, the black pupil on a white sclera.